2022
DOI: 10.1038/s41598-022-09923-1
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided side-fenestrated needle biopsy sampling is sensitive for pancreatic neuroendocrine tumors but inadequate for tumor grading: a prospective study

Abstract: Accurate pretreatment grading of pancreatic neuroendocrine tumors (PanNETs) is important to guide patient management. We aimed to evaluate endoscopic ultrasound-guided fine needle biopsy sampling (EUS-FNB) for the preoperative diagnosis and grading of PanNETs. In a tertiary-center setting, patients with suspected PanNETs were prospectively subjected to 22-gauge, reverse-bevel EUS-FNB. The EUS-FNB samples (Ki-67EUS) and corresponding surgical specimens (Ki-67SURG) were analyzed with Ki-67 indexing and thereafte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Studies of PanNETs with cytologic-histologic correlation, for instance, have generally found that grading on cytology material is significantly more likely to result in undergrading of cases than overgrading compared to surgical core biopsy or resection material. 9,10,[12][13][14][15][16][17] Case 25 was initially classified as low grade on the basis of review of the primary tumor resection, but when Ki67FNA from the lymph node metastasis was found to be high, rereview of the surgical material confirmed high-grade MTC in the lymph node metastases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies of PanNETs with cytologic-histologic correlation, for instance, have generally found that grading on cytology material is significantly more likely to result in undergrading of cases than overgrading compared to surgical core biopsy or resection material. 9,10,[12][13][14][15][16][17] Case 25 was initially classified as low grade on the basis of review of the primary tumor resection, but when Ki67FNA from the lymph node metastasis was found to be high, rereview of the surgical material confirmed high-grade MTC in the lymph node metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of limited sensitivity but high specificity for Ki67FNA echoes prior studies comparing cytology and surgical Ki67 PRs in neuroendocrine tumors from other organ systems. Studies of PanNETs with cytologic–histologic correlation, for instance, have generally found that grading on cytology material is significantly more likely to result in undergrading of cases than overgrading compared to surgical core biopsy or resection material 9,10,12–17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the studies, higher levels of concordance have been achieved when only samples with high cellularity were included, when the highest Ki-67 index was considered for grading, and for small lesions of less than 2 cm in diameter. Again, most pitfalls have been found for grade 2 tumours, which are often downstaged [ 83 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. An adequate sample size using a needle that allow a total length of the sample of at least 15 mm with prevalence of neoplastic tissue (>80%) should help in minimizing the risks of misinterpretation of tumour grade [ 36 ].…”
Section: Tumour Tissue Heterogeneity and The Impact On Biopsymentioning
confidence: 99%